(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2010)
Some important physico-chemical properties of water of major ponds of Comilla Town were studied to evaluate the water quality. Eight water samples were collected during the dry period (March 2005) from eight major ponds of Comilla Town (Ranir dighi, Mandir dighi, Nanuar dighi, Fauzdari dighi, Modina dighi, Dargabari dighi, Darma Sagar and Thakurpara). The result revealed that all the chemical constituents, except a few, are beyond the recommended limit for different uses. Higher value of pH (at Dargabari dighi, Darma Sagar dighi), OM (at Thakurpara dighi, Fauzdari dighi and Modina dighi), NH4+ concentration (at Ranir dighi, Mandir Dighi, Fauzdari dighi, Modina dighi and Dargabari dighi), and lower value of DO (at Fauzdari dighi and Modina dighi) may due to continuous disposal of kitchen wastes, organic wastes, sewage running and fall of twigs as well as extensive used for bathing, washing cloths and utensils etc. All indicate eutrophication and affect community health and hygiene and also create aesthetic problem in the locality. Key words: Ponds; Comilla District; Water quality Eutrophication DOI: 10.3329/bjsir.v45i1.5184 Bangladesh J. Sci. Ind. Res. 45(1), 57-62, 2010